Tingkat Kepuasan Penumpang Terhadap Kualitas Pelayanan Jasa Kereta Api Lokal Penataran Relasi Sidoarjo – Malang Kota Lama - Ismail, Ahmad Bagus; Setiono, Tonny Agus; Suraharta, I Made (Politeknik Perkeretaapian Indonesia Madiun, 2020)
The diversity of characteristics of passengers allows for different satisfaction ratings, whereas basically the railway operator must be able to create overall satisfaction for customers. Seeing the existing conditions on the Penataran Local Railway, the services provided to service users on the train are still not good considering the relatively high average occupancy. Therefore, it is necessary to know the level of passenger satisfaction with the service quality of the local train service upgrading the Sidoarjo - Malang Kota Lama relationship. This research was conducted to determine the level of passenger satisfaction with the descriptive analysis method of passenger characteristics. The customer satisfaction index is calculated using the CSI (Customer Satisfaction Index) analysis method. Assessment of the level of service provided by PT. KAI especially DAOP 8 Surabaya in terms of performance level and importance. The result can be seen that the level of service performance can be interpreted as quite satisfied, while the level of importance can be interpreted as important